Labor and educational careers of racialized youth in Catalonia from an intersectional perspective - Urdiales Correa, Josselyn; Castellanos, Rosa Lázaro (Critical Proposals in Social Work, 2021)
The Spanish immigration of the 1990s brought social, educational and labor transformations for the population in general and, in particular, challenges for the children of immigrant families. After three decades, it is generally held that the social, educational and labor market integration of immigrants’ children is favorable, although different from one of the young natives. This article will address, from an intersectional perspective, the educational and labor careers of young people of immigrant origin and racialized in Barcelona. From a qualitative research focused on the labor careers of these young people, we will show the restrictions of class, gender and origin in their professional promotion within an increasingly competitive and precarious labor market.